A novel wide‐band dielectric imaging system to guide radiofrequency ablation for pulmonary vein isolation. (26th October 2022) - Maurer, Tilman; Flindt, Max; Jularic, Mario; Lemes, Christine; Akbulak‐Stegli, Ruken Özge; Gunawardene, Melanie A.; Hartmann, Jens; Eickholt, Christian; Willems, Stephan; Schäffer, Benjamin
Abstract: Introduction: Recently, the wide‐band dielectric mapping system Kodex‐EPD was introduced. This study reports the first clinical experience using a novel system to guide pulmonary vein isolation (PVI) with radiofrequency (RF) ablation. Methods and Results: The study included 20 consecutive patients undergoing de‐novo PVI for symptomatic paroxysmal or persistent atrial fibrillation guided by Kodex‐EPD. The primary efficacy endpoint was successful PVI. Secondary endpoints included procedural parameters and complications. In all 20 patients (mean age 68 ± 8 years, 12 male patients, paroxysmal fibrillation in 14/20 [70%] patients), PVI was successfully completed. One patient underwent additional cavo‐tricuspid isthmus ablation for concomitant typical atrial flutter and one patient required additional ablation of a focal atrial tachycardia. A conventional three‐dimensional image of the left atrium as well as the innovative endocardial panoramic view were used to guide catheter manipulation and ablation. Median procedure time was 115 [1st; 3rd quartile 93, 75; 140] min and median total fluoroscopy time was 9.9 [9.7; 11.2] min, of which a median of 0.8 [0.6; 0.9] min was required to create left atrial maps. Complete left atrial imaging using Kodex‐EPD was achieved within a median of 7.1 [5.7; 8.3] min. Median RF ablation time was 45.1 [34.6; 58.7] min. No major complications were observed. Conclusion: RF ablation PVI guided by Kodex‐EPD seems safe and feasible. The system provides effective three‐dimensional guidance for PVI.